2019
DOI: 10.1016/j.polymer.2018.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigations of free radical photopolymerization: Inhibition and termination reactions

Abstract: In this work, the inhibition and termination reactions occurring throughout a free radical photopolymerization initiated by a type-I photoinitiator are studied by kinetic modeling. The role of the macroradicals as the main oxygen trapping agents during the inhibition time is identified, and the absence of primary radical consumption by oxygen can be related to a high initiation efficiency at early times. The ratio of the termination reactions reveals that bimolecular termination remains the principal pathway f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 92 publications
1
37
0
Order By: Relevance
“…In this study, β=0.61 (Figure S1), indicating a mostly bimolecular recombination termination at Rp max , in agreement with other works . However, during the process of photopolymerization, many phenomena affect the termination mechanisms and β actually varies.…”
Section: Resultssupporting
confidence: 91%
“…In this study, β=0.61 (Figure S1), indicating a mostly bimolecular recombination termination at Rp max , in agreement with other works . However, during the process of photopolymerization, many phenomena affect the termination mechanisms and β actually varies.…”
Section: Resultssupporting
confidence: 91%
“…The excessive PIs at the surface will also hinder the transmission of light into deeper layer and reduce the polymerization therein . Therefore, significant termination would occur when PIs are overdosed due to the biradical coupling, resulting in limited increase in Cs . The polymerization profiles of TetEGDA containing between 0.01 and 0.5 wt% R‐Cl under LED@400 nm are recorded in Figure and Figure S6, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…( 8)). At the end of the process, remaining nonreacted macroradicals n P  are trapped by occlusion in the polymer network underwent vitrification 17 This assumption was confirmed by modelling showed that the concentration of [] Bn RP is three orders of magnitude higher than that of [] An RP (figure S3 of ESI). Therefore, the very low proportion of An RPspecies is not represented in figure 6.…”
mentioning
confidence: 65%
“…More precisely, the effectiveness of PRT process depends on two factors: (i) consumption of photoinitiator molecules and (ii) competition between PRT and initiation reactions. This last factor can be expressed by a ratio between PRT and initiation rates 17 : 7) and these radicals are not involved in the PRT process.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation